2004
DOI: 10.1017/s1461145704004535
|View full text |Cite
|
Sign up to set email alerts
|

AR-A014418, a selective GSK-3 inhibitor, produces antidepressant-like effects in the forced swim test

Abstract: The mechanism by which lithium exerts either its anti-manic or antidepressant effects remains to be fully elucidated. Although lithium inhibits the enzyme glycogen synthase kinase-3 (GSK-3) at concentrations that are relevant for treatment of bipolar disorder, it is unclear whether GSK-3-related mechanisms are responsible for its therapeutic effects in the treatment of this disease. We report that AR-A014418 (a selective GSK-3 inhibitor) induces behavioural changes that are consistent with the effects of antid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
211
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(223 citation statements)
references
References 10 publications
10
211
0
2
Order By: Relevance
“…17 The major finding of this study is that three of the four GSK3B SNPs investigated are strongly associated with 4-week SSRI antidepressant therapeutic response. This association between the GSK3B genetic variants and therapeutic response to SSRIs is supported by data from animal studies showing that GSK3 inhibitors had antidepressant-like activity 10,11 and that fluoxetine inhibited GSK3B activity. 3 Furthermore, a recent study of Italian bipolar depression patients found that the C/C homozygote for the GSK3B rs334558 polymorphism (À50C/T) SNP showed acute effects of total sleep deprivation treatment on perceived mood.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…17 The major finding of this study is that three of the four GSK3B SNPs investigated are strongly associated with 4-week SSRI antidepressant therapeutic response. This association between the GSK3B genetic variants and therapeutic response to SSRIs is supported by data from animal studies showing that GSK3 inhibitors had antidepressant-like activity 10,11 and that fluoxetine inhibited GSK3B activity. 3 Furthermore, a recent study of Italian bipolar depression patients found that the C/C homozygote for the GSK3B rs334558 polymorphism (À50C/T) SNP showed acute effects of total sleep deprivation treatment on perceived mood.…”
Section: Discussionmentioning
confidence: 76%
“…9 Thirdly, two studies in 2004 demonstrated that rats treated with GSK3 inhibitors showed reduced duration of immobility when exposed to the forced swim test, a well-established model for antidepressant efficacy, suggesting the potential of GSK3 inhibitors as antidepressants. 10,11 Finally, a recent post-mortem study demonstrated that there was no change in GSK3B protein levels in the ventral prefrontal cortex of MDD patients but that GSK3B activity increased significantly compared with control subjects. 12 The human GSK3B, located on chromosome 3q13.33, is about 268 kb in length and includes 12 exons.…”
Section: Introductionmentioning
confidence: 99%
“…However, additional effects of lithium on glutamate release or reuptake, or postsynaptic effects on glutamate receptors, downstream signaling, or direct effects on the receptor cannot be excluded. Recent data have suggested that lithium exerts some of its behavioral actions through inhibition of GSK-3 (Beaulieu et al, 2004;Gould et al, 2004;Kaidanovich-Beilin et al, 2004;O'Brien et al, 2004). Future studies will examine the link between GSK-3 inhibition and regulation of AMPA receptors.…”
Section: Discussionmentioning
confidence: 98%
“…For example, lithium, GSK-3b knockout and other GSK-3 inhibitors show antidepressant effects in rodents. [39][40][41] Lithium and other GSK-3 inhibitors also attenuate the hyperactivity induced by amphetamine in rats 40 or dopamine transporter knockout in mice. 42 Valproic acid-induced promoter IV activation is mimicked by treatment with other HDAC inhibitors, SB and TSA, or by gene knockdown with HDAC1-specific siRNA (Figure 5), suggesting the involvement of HDAC inhibition.…”
Section: Discussionmentioning
confidence: 99%